Arte y liturgia en la corte madrileña de los Borbones: rituales nobiliarios en la Casa Ducal de Medinaceli - Romero Medina, Raúl (Hispania sacra, 2021)
Art and liturgy in the Madrid Court of the Bourbons: nobiliary rituals in the ducal house of Medinaceli: The sacrament of baptism and confirmation of a member of the Ducal House of Medinaceli, firstborn or not, was during the Modern Age an important occasion to appear in society as members of an aristocratic hierarchy. Thus, the rituals around death and its funeral apparatus. In the same way, the decoration of the palace and the parish was key to all for its rich furniture and textile ornaments. Thus, in the mid-eighteenth century, Don Pedro de Alcántara Fernández de Córdoba y Moncada, XII Duke of Medinaceli, ordered to collect in writing the protocol to celebrate the rituals of his House. The analysis of this unpublished document focuses our attention to reflect on art and ritual in the context of the Madrid Bourbon Court.